Temporal dynamic vulnerability – impact of antecedent events on residential building losses to wind storm events in Germany - A. Trojand; H. W. Rust; H. W. Rust; U. Ulbrich (Natural Hazards and Earth System Sciences, 2025)
Severe winter storm events are one of central Europe's most damaging natural hazards and are therefore particularly in focus for disaster risk management. One key factor for risk is vulnerability. Risk assessments often assume vulnerability to be constant. This is, however, not always a justifiable assumption. This work seeks and quantifies a potential dynamic of vulnerability for residential buildings in Germany. A likely factor affecting the dynamics of vulnerability is the hazard itself (Aerts et al., 2018). As extreme events may destroy the most vulnerable elements, it is likely that the subsequent rebuilding or repair will reduce their vulnerability to following events (UNISDR, 2017). Therefore, the intensity of the previous events and the resulting damage can be assumed to be a decisive factor in changing vulnerability. A second important factor is the time period between the previous and current event. If the next event occurs during the reconstruction phase, vulnerability might be higher than when the reconstruction phase is completed (de Ruiter et al., 2020).